Phenolic Compounds and Hepatoprotective Activity of Chicory Herb Extract - O. L. Saybel; A. I. Radimich; T. D. Dargaeva; I. A. Lupanova; E. V. Ferubko; E. N. Kurmanova; I. A. Martynchik (Разработка и регистрация лекарственных средств)
Introduction. Chicory (Cichorium intybus L.) is widely applied for liver disease treatment by traditional medicine of different countries; as well, it is the object for pharmacological research of hepatoprotective activity. In this regard, the method for obtaining dry extract of wild chicory herb (WCHE) is developed in the All-Russian Research Institute of Medicinal and Aromatic Plants.Aim. Aim of the research is determination of the qualitative composition of phenolic compounds, identification of the substances prevailing in WCHE and conducting pharmacological screening of the extract.Materials and methods. WCHE chemical composition has been explored with HPLC-MS/MS method; the main components were determined quantitatively with HPLC-UF method using single compounds that were isolated by us earlier and identified by NMR spectroscopy. WCHE pharmacological screening of hepatoprotective activity research was involving 50 male rats. Acute toxic hepatitis in animals was induced by a single subcutaneous injection of 50 % oily solution of tetrachloromethane (TCM) at a dosage of 0.4 ml per 100 g body weight. One hour before administration TCM, animals received WCHE at the doses of 100 or 500 mg/kg. 48 hours after TCM administration, the activity of serum enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), as well as the content of total bilirubin were determined for preliminary establishment of pharmacological activity. Pathomorphological studies of rat liver were carried out using histological methods. The liver histological structure was inspected using liver sections stained with hematoxylin and eosin.Results and discussion. The component composition of WCHE is represented by oxycoumarins, hydroxycinnamic acids and flavonoids. The dominant phenolic compounds are esculetin, chicoriin, chicoric, chlorogenic and caftaric acids. It was found under acute experimental toxic hepatitis, that preliminary WCHE administration reduces the toxic TCM effect on liver cells. In animals treated with WCHE at doses both 100 mg/kg and 500 mg/kg body weight, it was observed decreases in ALT activity by 35 % and 45 %, AST by 15 % and 28 %, alkaline phosphatase by 15 % and 21 %; the content of total bilirubin by 20 % and 29 %, respectively, in comparison with similar indicators in the group of animals that were not treated with the extract. The histological study showed that WCHE administration to animals at the doses of 100 and 500 mg/kg reduces dystrophic changes in hepatocytes, this effect is more pronounced at the extract dosage of 500 mg/kg.Conclusion. Main WCHE components are oxycoumarins (esculetin, chicoriin), hydroxycinnamic acids (chicoric, chlorogenic and caftaric). According to the results of screening studies, it was established that WCHE in doses of 100 mg/kg and 500 mg/kg is a promising object for further pharmacological research.